Investigftion of casting material from heat resisting nickel alloy after hot isostatic pressing and heat treatment - Жеманюк, П. Д.; Клочихин, В. В.; Лысенко, Н. А.; Наумик, В. В. (Eastern-European Journal of Enterprise Technologies, 2013)
In the process of blades hot isostatic pressing (HIP) occurs the "healing" of micropores and friables, which are not coming to the surface of parts, what results in stabilize of the material structure and properties. For the material of blades and specimens after HIP is typical the structural un-homogeneity as the result of the «raft»-structure creating shaped as the zonal parts in the plaices of pores "healing" and around of carbides МС-typ. The subsequent thermal treatment enhances the structural homogeneity of the alloy, stress relaxation and a positive effect on plasticity characteristics of the alloy while maintaining the strength and heat resistant properties. HIP processing and the subsequent homogenization provide the most favorable reception of strength, plastic properties and long-term strength.